Necesidad de una protección adecuada a los defensores y defensoras de derechos humanos ambientales - Gamboa Balbín, Aída Mercedes (2022)
The threats due to illegal logging, illegal mining, illegal agriculture and illicit cultivation of coca come together in the Amazon and in Peru. Such activities daily increase environmental defenders’ vulnerability level. They are subject to aggressions when defending and protecting their lands and natural resources. This panorama has been aggravated by the arrival of the pandemic and was complemented by incentive to extractive and infrastructure activities, resulting in the continuity of socio-environmental conflicts, such as escalation of violence and criminalization of environmental defenders. Murders have increased and have been reported by various international and domestic organizations, despite progress in the justice and environment sectors. Therefore, there is need for adequate implementation of various existing tools and also for the Congress of the Republic to ratify the Escazú Agreement, the first environmental treaty containing provisions for effective protection of these people.